Motivasi Orang Tua Dan Pemilihan Jenis Sekolah: Studi Kasus Keluarga Departemen Agama Kota Administratif Jember: Parental Motivation and School Type Selection: A Case Study of Families in the Department of Religious Affairs, Jember Administrative City - Sofyan Tsauri (Fenomena, 2002)
Parental influence on children’s educational decisions often prioritizes academic excellence over democratic choice, potentially undermining children’s learning autonomy. This study examines the underexplored relationship between parenting motivation styles and children’s preferences for general versus vocational schools. Using a quantitative descriptive approach, data were collected from 110 parents working at the Department of Religious Affairs in Jember through questionnaires, interviews, and documentation. Chi-square and contingency coefficient analyses revealed significant associations between motivation styles and school choice. Children of authoritarian parents tended to prefer vocational schools, whereas those with democratic or permissive parents leaned toward general schools. The strength of the relationship was moderate to strong (KK between 0.42 and 0.50). The study concludes that democratic motivation fosters alignment with children’s interests, whereas authoritarian styles limit choice. Recommendations include structured parental guidance on motivation strategies and improved awareness of children’s aptitudes and family financial realities to support optimal educational decisions. Pengaruh orang tua terhadap keputusan pendidikan anak sering mengutamakan prestasi akademik daripada pilihan demokratis, yang berpotensi mengurangi otonomi belajar anak. Penelitian ini mengkaji hubungan antara gaya motivasi orang tua dan preferensi anak terhadap sekolah umum versus kejuruan. Dengan pendekatan deskriptif kuantitatif, data dikumpulkan dari 110 orang tua pegawai Departemen Agama di Jember melalui angket, wawancara, dan dokumentasi. Analisis Chi-kuadrat dan koefisien kontingensi menunjukkan adanya hubungan signifikan antara gaya motivasi dan pilihan sekolah. Anak dari orang tua otoriter cenderung memilih sekolah kejuruan, sementara anak dari orang tua demokratis atau permisif cenderung memilih sekolah umum. Kekuatan hubungan tergolong cukup kuat (KK antara 0,42 dan 0,50). Kesimpulannya, motivasi demokratis mendukung kesesuaian dengan minat anak, sedangkan gaya otoriter membatasi pilihan. Rekomendasi mencakup bimbingan terencana tentang strategi motivasi serta peningkatan kesadaran akan bakat anak dan kemampuan finansial keluarga.